The relationship of children connectivity and physical activities with satisfaction of open spaces in high rise apartments in Tehran - Sharghi, Ali; Maulan, Suhardi; Salleh, Ilias; Syed Salim, Azizah Salim (Australian International Academic Centre, 2014)
Increase of urbanization has pressure on the urban children's lives and physical activities. While in designing of residential apartments’ open spaces, there is little attention to the children. The children, who live in the high-rise apartments found to have less physical activities. However, supposedly, children need to engage in the physical activity in the outdoor areas as WHO recommend that children take part in at least one hour of moderate physical activity in every day. This paper firstly, reviews different researches in this area. Then, it attempts to find children’s satisfaction regarding connectivity to open spaces as a dependent variable and their preferred activities, perceived safety, and familiarity about connectivity to open spaces as independent variables. The method of study is a semi-interview survey with 80 children between 6 and 12 years old (primary school ages) in two cases in Tehran. The result of this research shows that children satisfaction from open space has an effect on their outdoor activities. Therefore, the designers should be considering children physical activities needs in open spaces.